Pre Medication With Midazolam in Children For Smooth Separation From Parents: A Comparison Of Two Different Routes of Administration (Journal of Chittagong Medical College Teachers' Association, 2017)
Premedication with midazolam is widely used in paediatric anaesthesia to reduce fear, anxiety, emotion, psychological trauma and ensure smooth separation from parents. However, various routes and dosing regimens are recommended for paediatric premedication and variable efficacy is found when use in different routes. The aim of our study to compare the efficacy and acceptable route between intranasal versus sublingual midazolam premedication for smooth separation from parents before entering the operation theater. It will be a comparative, cross-sectional prospective clinical study. 120 unmedicated children, ASA I or II, Age 1–6 years, who will be scheduled for routine elective surgery and who will be planned to receive midazolam as a premedicant drug, will be randomly assigned to one of the two groups. Group–I receives intranasal midazolam 0.2 mg kg-1 and Group–II receives sublingual midazolam 0.2 mg kg-1 after having obtained the parent’s informed consent. Heart rate, Systolic blood pressure, SpO2, Sedation and Anxiolysis Scores will be assessed in 4-point scale by the anaesthesiologist every 3 min prior to surgery. Sixty patients will be enrolled in each group, I and II. Data will be compiled and analyzed in computer, using statistical software package SPSS.JCMCTA 2016 ; 27 (2) : 24 - 30